2014
DOI: 10.1021/nl5024194
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Strain Engineering on the Surface of a Bulk TiO2 Crystal

Abstract: Arrays of highly strained 5-25 nm-wide regions have been prepared on rutile TiO2(110) surface through a low energy Ar ion bombardment technique. Using scanning tunneling microscopy (STM) and an innovative STM tip-triggered nanoexplosion approach we show experimentally that the protrusions arise from subsurface Ar-filled pockets. Continuum mechanics modeling gives good estimates of the corresponding elastic deformation. Surface strain values of up to 4% have been deduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
46
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 32 publications
3
46
0
1
Order By: Relevance
“…To date, numerous approaches have been developed to induce surface strains. Examples include introducing a subsurface inert gas by low‐energy inert ion bombardment, physical stretching of the support substrate, and extracting and intercalating ions in layered structures to induce crystal structure changes . However, most strain‐related catalysis previously reported involves heterogeneous catalysts .…”
Section: Introductionmentioning
confidence: 99%
“…To date, numerous approaches have been developed to induce surface strains. Examples include introducing a subsurface inert gas by low‐energy inert ion bombardment, physical stretching of the support substrate, and extracting and intercalating ions in layered structures to induce crystal structure changes . However, most strain‐related catalysis previously reported involves heterogeneous catalysts .…”
Section: Introductionmentioning
confidence: 99%
“…Ar + ion sputtering has been used more recently [5] to distribute stress across Au(100) surfaces and an increase in chemical reactivity was seen at the defected, or locally stressed, sites. Strain has also been seen across the surfaces of metallic nanoparticles -for example, Pd@Pt [6], Pt [7] and Au [8][9] -and both oxide nanoparticles and thin-films [10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an amount of research has been dedicated to enhancing the visible-light activity of TiO 2 photocatalysts, by narrowing the band gap, and sensitizing with the semiconductors of narrow band gap [7][8][9][10]. Recently, it has been shown that manipulating structure morphology and electronic structure are effective approaches to improve the separation and transportation of charge carriers [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%